The role of national human rights institutions in promoting and protecting the rights of refugees: the case of South Africa and Kenya - John-Langba, Vivian Nasaka (University of Cape Town, 2020)
The apparent normative and implementation gaps within the international refugee protection regime suggest the need to reform its implementation and accountability processes. Increasingly, the focus is being shifted to local or domestic actors to attempt to address the challenges faced in realising refugee rights effectively. Among the key domestic accountability actors for the realisation of rights, are national human rights institutions (NHRIs). NHRIs are considered a bridge between the international and domestic human rights systems. NHRIs act as entities that facilitate the diffusion of international human rights norms and standards, including those with respect to refugee rights, into the national spheres. Notwithstanding this, there is paucity in empirical evidence within the refugee rights discourse on the role that NHRIs can play to promote the effective realisation of refugee rights. This study explores the role that NHRIs in South Africa and Kenya play in promoting and protecting refugee rights. It utilises a non-doctrinal and qualitative research approach, to examine the extent to which the NHRIs engage with refugee rights and to explore their capacity to do so effectively. It situates NHRIs within the nexus between international human rights law and international refugee law to frame the understanding for their role within the refugee protection regime. The findings indicate that the NHRIs in South Africa and Kenya that are compliant with the Paris Principles display significant engagement with refugee rights promotion and protection. As accountability mechanisms, they have contributed to the development and implementation of domestic refugee law and policy in accordance with international norms and standards. This has occurred despite the lack of an explicit refugee rights' promotion and protection mandate, but they face barriers and challenges. Various underlying factors that impede their effectiveness to address refugee rights were identified. These included the sociopolitical contexts within which they operate, capacity constraints and invisibility within the refugee protection regime. The socio-political challenges included xenophobia and the securitisation of the asylum space. These compounded organisational and operational weaknesses such as scarce specialist skills in refugee law, limited financial resources, and the absence of strategic and sustained partnerships for refugee rights protection. The overall absence of norms for NHRI engagement with refugee rights was identified as a contributory factor for the lack of a coherent approach for promoting and protecting these rights. Possible avenues to enhance NHRI engagement with refugee rights were identified. For instance, NHRIs building partnerships for refugee rights promotion and protection with CSOs, the UNHCR and regional institutions based on a clear understanding of an NHRI's role as accountability mechanisms. For NHRIs, the imperative lies in building their capacity to address refugee rights to ensure a clear understanding of what the promotion and protection of these rights entails.